2022
DOI: 10.1177/24715492221090762
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Pulmonary Nodules Found on Shoulder Arthroplasty Preoperative CT Scans

Abstract: With current emphasis on preoperative templating of anatomical and reverse shoulder arthroplasty (aTSA and rTSA, respectively), patients often receive thin slice (<1.0 mm) computerized tomography (CT) scans of the operative shoulder, which includes about two-thirds of the ipsilateral lung. The purpose of this study is to evaluate the prevalence and management of incidentally detected pulmonary nodules on preoperative CT scans for shoulder arthroplasty. In this single-center retrospective study, we queried r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Although this rate is similar to our reported overall rate of incidental findings (23.7%), the study by Lopez et al [ 8 ] was limited to pulmonary nodules and did not account for alternative incidental findings. Thus, the rate of pulmonary nodules reported by Lopez et al [ 8 ] is much higher than what was observed in our patient cohort, as only 59% of incidental findings were pulmonary in nature. Given our inclusion of all types of incidental findings, our study represents a valuable addition to the current literature on this subject.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although this rate is similar to our reported overall rate of incidental findings (23.7%), the study by Lopez et al [ 8 ] was limited to pulmonary nodules and did not account for alternative incidental findings. Thus, the rate of pulmonary nodules reported by Lopez et al [ 8 ] is much higher than what was observed in our patient cohort, as only 59% of incidental findings were pulmonary in nature. Given our inclusion of all types of incidental findings, our study represents a valuable addition to the current literature on this subject.…”
Section: Discussionsupporting
confidence: 90%
“…Most published studies have focused on pulmonary incidental findings or aimed to compare the incidence of these findings on different imaging techniques. Lopez et al [ 8 ] demonstrated that 22.8% of patients undergoing TSA had pulmonary nodules incidentally detected on preoperative shoulder CT. Although this rate is similar to our reported overall rate of incidental findings (23.7%), the study by Lopez et al [ 8 ] was limited to pulmonary nodules and did not account for alternative incidental findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations